2019
DOI: 10.3762/bjoc.15.234
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-derived oxazolone pseudotetrapeptide as γ-turn inducer and anion-selective transporter

Abstract: The intramolecular cyclization of a C-3-tetrasubstituted furanoid sugar amino acid-derived linear tetrapeptide afforded an oxazolone pseudo-peptide with the formation of an oxazole ring at the C-terminus. A conformational study of the oxazolone pseudo-peptide showed intramolecular C=O···HN(II) hydrogen bonding in a seven-membered ring leading to a γ-turn conformation. This fact was supported by a solution-state NMR and molecular modeling studies. The oxazolone pseudotetrapeptide was found to be a better Cl−-se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…This was also supported by DFT calculation studies which showed the g-turn conformation stabilized by an intramolecular (II)NHÁ Á ÁOQC hydrogen bonding in a sevenmembered ring. 116 Among 11a and 11b, only 11a showed significant ion transport activity, which indicates that the amino group is necessary for the desired ion transport. Furthermore, the precursor of 11a, the compound that does not contain the oxazolone ring and lacks the g-turn did not show any ion transport activity, indicating the importance of the ring for inducing the g-turn in 11a which eventually leads to anionselective ion transport across the lipid bilayer membrane.…”
Section: B Ion Channels Containing Fluorinated Sugar Amino Acid Backbonementioning
confidence: 98%
“…This was also supported by DFT calculation studies which showed the g-turn conformation stabilized by an intramolecular (II)NHÁ Á ÁOQC hydrogen bonding in a sevenmembered ring. 116 Among 11a and 11b, only 11a showed significant ion transport activity, which indicates that the amino group is necessary for the desired ion transport. Furthermore, the precursor of 11a, the compound that does not contain the oxazolone ring and lacks the g-turn did not show any ion transport activity, indicating the importance of the ring for inducing the g-turn in 11a which eventually leads to anionselective ion transport across the lipid bilayer membrane.…”
Section: B Ion Channels Containing Fluorinated Sugar Amino Acid Backbonementioning
confidence: 98%